Tridirectional association between probable depression, fear of falling and falls among middle-aged and older adults in Thailand - Pengpid S. (2023)
Purpose: Depression is a major issue in the aging population, which may be related to fear of falling (FOF) and falls contributing to increased morbidity and mortality. The aim of the study was to assess the tridirectional associations between probable depression (PD), FOF and falls in a longitudinal study in Thailand. Methods: Longitudinal data of participants (≥45 years; N = 3708) from two consecutive waves (in 2015 and 2017) of the Health, Aging and Retirement in Thailand (HART) study were analysed. PD was assessed with the Center for Epidemiologic Studies Depression Scale, self-reported FOF and history of falls. Results: Having no PD in 2015 and PD in 2017 (aOR: 2.35, 95% CI: 1.67 to 3.30), and having both PD in 2015 and 2017 (aOR: 3.46, 95% CI: 1.92 to 6.23) were positively associated with incident FOF with activity avoidance, and no FOF in 2015 and FOF in 2017 (aOR: 2.29, 95% CI: 1.77 to 2.95), and both FOF in 2015 and 2017 (aOR: 2.38, 95% CI: 1.69 to 3.36) were positively associated with incident PD. Two or more falls in 2015 (aOR: 2.03, 95% CI: 1.29 to 3.19) was positively associated with incident PD, and both PD in 2015 and 2017 (aOR: 3.10, 95% CI: 1.40 to 6.48) were positively associated with incident multiple (≥2) falls. Conclusions: We found tridirectional associations between PD, FOF and falls. It is suggested to screen and manage older adults for PD, FOF and fall history simultaneously.